Laser Induced Damage Studies on Al2O3, SiO2, and MgF2 Thin Films for Anti-Reflection Coating Application in High Power Laser Diode - C.J. Panchal; M.S. Desai; A.L. Patel; G.G. Bhatt (Журнал нано- та електронної фізики)
The laser diode facet damage is one of the impeding factors of the high-power laser diode operation. To overcome this restriction laser diode facet coating can be utilized. During the high power operation of the laser diode, it is observed that the single layer anti reflection (AR) coating at the front facet shows optical damage while the multilayer high reflective coating at the back facet remains undamaged. To determine the “damage threshold” of the materials used for AR coating, an e-beam evaporated Al2O3, MgF2, and SiO2 single layer thin films on GaAs substrate have been optimized for the wavelength ~ 1060 nm. The diode pumped Q-switched Neodymium Yttrium Aluminum Garnet (Nd:YAG) laser (1064 nm) was used to da-mage the samples. The damage on the sample was observed under the microscope. The effective damage radius on the samples was 150 m and average continuous wave laser induced damage threshold was found  10 W.